Chemical characterization and antioxidant properties of Lepista nuda fruiting bodies and mycelia obtained by in vitro culture: effects of collection habitat and culture media - Pinto, Sara Vanessa da Cruz (2013)
Lepista nuda is an edible mushroom which presents important organoleptic qualities including a delicate flavor and good postharvest conservation. Its chemical and bioactive properties can be affected by habitat collection. Therefore, the main goal of the present work was to compare chemical composition and antioxidant potential of Lepista nuda samples from different habitats, and mycelia produced by in vitro culture, using different culture media. The commercial sample (cultivated) gave the highest levels of energy, polyunsaturated fatty acids (due to the contribution of linoleic acid) and phenolic compounds; the wild sample from oak forest gave the highest levels of organic acids. Mycelia samples showed higher levels of glucose, tocopherols and antioxidant activity. Particularly, PACH (Pachlewski medium) proved to be better for glucose production, PDA (Potato Dextrose Agar medium), PACH and FAD (Ferry & Das medium) for β- and γ-tocopherols, complete MMN (Melin-Norkans medium) for phenolic compounds and incomplete MMN for antioxidant properties. Overall, in vitro culture could be explored to obtain bioactive compounds from macrofungi for industrial applications, controlling environmental conditions to produce higher amounts of these compounds and to overcome the diversity in chemical composition observed in samples collected in different habitats.